Pendidikan Jasmani Adaptif Bagi Guru MGMP PJOK Kabupaten Karo Dalam Mendukung Pembelajaran Inklusi - Gita Nurgaya Br Tarigan; Wulandari Putri Lagenda; Aidilla Pratiwi Siregar; Arsi Zahiri; M. Fadlin Al-Farhan's (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: This study aimed to evaluate the effectiveness of a practice-based training and collaborative mentoring program in enhancing adaptive physical education competencies among Physical Education, Sports, and Health (PJOK) teachers to support inclusive teaching practice. Materials and methods: A practice-based professional development program was implemented involving 32 junior and senior high school PJOK teachers participating in the Subject Teacher Forum (MGMP) in Karo Regency, Indonesia. The intervention integrated needs assessment, conceptual workshops, adaptive game modification, lesson-plan development, microteaching, reflective mentoring, and collaborative discussions. Program effectiveness was evaluated using a one-group pretest–posttest approach through knowledge assessments, adaptive teaching-plan evaluations, structured microteaching observations, and participant satisfaction questionnaires. Quantitative data were analyzed descriptively using percentage scores and normalized gain (N-gain), while qualitative reflections were analyzed thematically. Results: The findings demonstrated substantial improvements in teachers' adaptive physical education competencies following the intervention. Mean knowledge scores increased from 58.28 to 84.84, with an N-gain of 0.64, indicating moderate-to-high learning improvement. The quality of adaptive teaching plans improved from an average score of 60.16 to 86.41, while microteaching performance achieved a mean score of 3.42 (Good category). Furthermore, 90.63% of participants reported that the program was highly relevant to their instructional needs. The most notable improvements were observed in teachers' abilities to modify learning objectives, instructional strategies, equipment, learning environments, assessment methods, and classroom participation to accommodate diverse learner needs. Conclusions: Practice-based training combined with collaborative mentoring effectively strengthened teachers' readiness and adaptive pedagogical competencies for inclusive physical education. The findings suggest that experiential professional development embedded within teacher learning communities can bridge the gap between inclusive education policies and classroom implementation. Sustaining this approach through continuous MGMP-based professional learning communities may contribute to the long-term implementation of inclusive physical education in mainstream schools.